2008
DOI: 10.1016/j.bbi.2007.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and immunosuppression during stress: Relationship conflict or energy conservation?

Abstract: Despite the apparent health benefits of social relationships, some studies indicate that larger social networks can be associated with greater vulnerability to infectious disease, particularly if stressors are also present. Two possibilities for such effects are, first, that more social contacts lead to more negative affect and social conflict during stressors, or second, that maintaining more social contacts is an energetically costly activity, and ecologically motivated immunosuppression is one means of prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…For example, stress has been associated with increased release of pro-inflammatory neuropeptides by the airway-innervating autonomic nerves [41], with amplification of delayed-type hypersensitivity responses [42], and with increased airway inflammation after allergen exposure [43]. Moreover, immune cells from stressed individuals show a cytokine release profile suggestive of enhanced allergic activity (e.g., Th2-shifted) [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…For example, stress has been associated with increased release of pro-inflammatory neuropeptides by the airway-innervating autonomic nerves [41], with amplification of delayed-type hypersensitivity responses [42], and with increased airway inflammation after allergen exposure [43]. Moreover, immune cells from stressed individuals show a cytokine release profile suggestive of enhanced allergic activity (e.g., Th2-shifted) [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the US, most adults are assumed to have competent cell-mediated immune responses, and DTH to tuberculin purified protein derivative (PPD) is used to screen for Mycobacterium tuberculosis exposure (Lee and Holzman, 2002). Conversely, DTH testing with an antigen to which exposure can be assumed, such as the ubiquitous fungal pathogen, Candida albicans , is used to evaluate CMI (e.g., Edelman et al, 1973; Segerstrom, 2008) . C. albicans is the causative agent of “thrush” (oral candidiasis) and “yeast infection” (vaginal candidiasis); among severely immunocompromised individuals, it can cause life-threatening systemic infection (candidemia).…”
mentioning
confidence: 99%
“…Among first-year law students, relocation to attend law school and attendant separation from established social networks was associated with better cellular immunity as measured by delayed-type hypersensitivity (DTH) testing. Within-person changes in social network size across the first six months of law school paralleled this betweenperson finding: at those assessment points when a student had more social contacts, he or she also had poorer cellular immunity [9]. Although there might be a psychological benefit to tonic and phasic engagement with one's social network, there also appears to be an immunological cost associated with maintaining network contacts while also meeting the demands of law school.…”
Section: Social Network Energy and Immunitymentioning
confidence: 79%
“…There are, however, some unusual and perplexing findings with regard to the effects of social networks on immune function. Larger social networks have associated with poorer cellular immunity in healthy young adults and HIV patients [8,9]. One study found that the increased risk of upper respiratory infection that accompanies severe life stressors increased further for those people with large social networks [10].…”
Section: Introductionmentioning
confidence: 98%